The Eurozone as an Inflation Target Zone - Pompeo Della Posta; Roberto Tamborini (Center for Economic Studies and ifo Institute (CESifo), 2022)
In the revised monetary policy strategy of the European Central Bank (ECB), "price stability is best maintained by aiming for two per cent inflation over the medium term", with "symmetric commitment" to this target. "Symmetry means that the Governing Council considers negative and positive deviations from this target as equally undesirable". In this article, we therefore analyse this policy strategy through a model of inflation target zone, with a central value and symmetric upper and lower bounds on inflation, within which the central bank may decide not to intervene, provided inflation is expected to fluctuate around the central value. We show that the policy benefits guaranteed by a target zone can be dissipated if market agents are uncertain about its width.
Keywords: E31; E42; 330; European Central Bank; monetary policy strategy; inflation target zones